Postnaturalism in the narratives of two cultures, or why the crisis of the civilization is inevitable - Weiner, January (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Recenzja książki: Ewa Bińczyk, Epoka człowieka. Retoryka i marazm antropocenu, Wydawnictwo Naukowe PWN, Warszawa, 2018, ss. 325.
Keywords: anthropocene